Ventajas y desventajas de vincular laboralmente teletrabajadores en condición de discapacidad en el sector salud de Bogotá (2017)
In the present monograph the teleworking modality in Colombia is studied, analyzing and defining each of the aspects that must be taken into account when implementing this modality in an organization, in addition to the necessary technological, legal and health considerations; In addition, the advantages and disadvantages are described and analyzed for both the teleworker and the company when deciding to implement teleworking in the organization, it should be noted that they apply both for teleworkers in a disability condition and for those who are not in that condition.